Participation of Students with Special Educational Needs (SEN) in Extracurricular Activities in Compulsory Education - Macarena Castellary-López; Victoria Figueredo-Canosa; Juan Rafael Muñoz-Muñoz; Luis Ortiz-Jiménez (MDPI AG, 2023)
Within the R + D + I project "Study of the educational response to students with Specific Need of Educational Support hereinafter (SEN) associated with disability", one of the areas analyzed covers extracurricular and complementary activities and if these meet the needs of students with specific educational support needs. Our objective in this research is to describe and analyze the inclusion of students with SEN associated with disability in the development of extracurricular activities. A total of 1496 teachers from Spain participated in this study, answering a questionnaire prepared ad hoc. The independent variables in the study were sex, type of center (rural or urban) and ownership (public or private). The results showed that the teachers consider that most of the centers allow the participation in extracurricular activities of the students with SEN; in parallel, it was discovered that these centers are not fully equipped to serve students with SEN.